Uncovering a New Moral Dilemma of Economic Optimization in Biotechnological Processing. - Vochozka, Marek; Stehel, Vojtěch; Maroušková, Anna (Science & Engineering Ethics, 2018)
The trend of emerging biorefineries is to process the harvest as efficiently as possible and without any waste. From the most valuable phytomass, refined medicines, enzymes, dyes and other special reactants are created. Functional foods, food ingredients, oils, alcohol, solvents, plastics, fillers and a wide variety of other chemical products follow. After being treated with nutrient recovery techniques (for fertilizer production), biofuels or soil improvers are produced from the leftovers. Economic optimization algorithms have confirmed that such complex biorefineries can be financially viable only when a high degree of feedstock concentration is included. Because the plant material is extremely voluminous before processing, the farming intensity of special plants increases in the nearest vicinity of agglomerations where the biorefineries are built for logistical reasons. Interdisciplinary analyses revealed that these optimization measures lead to significantly increased pollen levels in neighbouring urban areas and subsequently an increased risk of allergies, respectively costs to the national health system. A new moral dilemma between the shareholder’s profit and public interest was uncovered and subjected to disputation.